Implementasi Metode Pembelajaran Satu Bulan Bisa Baca dalam Menumbuhkan Cinta Buku pada Siswa Taman Kanak-Kanak Islam Terpadu Ar Raihan Kota Pagar Alam - Hudayah, Khairani (UIN Fatmawati Sukarno Bengkulu, 2025)
This study examines the implementation of the One Month Can Read (SB3) learning method in cultivating book affection among early childhood students at TKIT Ar Raihan, Pagar Alam City. While the SB3 method is renowned for its effectiveness in accelerating children's reading skills, this research specifically explores its impact on developing children's interest and love for books. Using a qualitative case study approach, data were collected through participatory observation, in-depth interviews with teachers, parents, and students, as well as analysis of supporting documents such as lesson plans and children's work. The findings reveal that the SB3 method successfully creates an enjoyable and interactive learning environment where children not only learn to read quickly but also develop a strong interest in books. Key supporting factors include the use of engaging learning media, teachers' active role in storytelling, and parental involvement in accompanying children's reading activities at home. However, challenges such as time constraints and varying levels of children's comprehension were also identified. Overall, the SB3 method proves effective not only in enhancing reading skills but also in instilling reading habits and fostering book affection from an early age.